2005
DOI: 10.1021/jp040251k
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Ion/Molecule Reactions in C5F8

Abstract: Gas-phase ion-molecule reactions in octafluorocyclopentene (C5F8) were studied with a pulsed electron beam mass spectrometer. When a few Torr of major gas, CH4, Ar, or N2, containing approximately 10 mTorr C5F8 was ionized by 2 keV electrons, C5F8+, C5F7+, C4F6+, C4F5+, and C3F3+ were formed as major fragment ions. The interaction between those ions and C5F8 is found to be a weak electrostatic interaction. The cation...C5F8 bonding energies are around 10 kcal/mol, which were reproduced well by (U)B3LYP/6-311+G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…± 0.7 eV, while Hiraoka et al 12 calculated the IE to be 11.2 eV using B3LYP methods. To verify these values, we have performed a new electron ionisation study at the Institut für Ionenphysik in Innsbruck, 34 and a He(I) photoelectron spectrum has been recorded at the University of Southampton.…”
Section: Energeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…± 0.7 eV, while Hiraoka et al 12 calculated the IE to be 11.2 eV using B3LYP methods. To verify these values, we have performed a new electron ionisation study at the Institut für Ionenphysik in Innsbruck, 34 and a He(I) photoelectron spectrum has been recorded at the University of Southampton.…”
Section: Energeticsmentioning
confidence: 99%
“…The second study investigated cation and anion molecule reactions in a high pressure environment. 12 One aim of this work is to gain insight into how electron transfer occurs in bimolecular reactions.…”
mentioning
confidence: 99%
“…1. Figure 2 shows the temperature dependence of the rate constants for reaction (5) measured in the temperature range of 180῎310 K. Although the data points are rather scattered due to the di$culty in maintaining the steady-state experimental conditions (charging of the ion source), the rate constants for reaction (5) are found to be independent on the ion source temperature in the range of 180῎310 K. It was confirmed that the second-order rate constants for reaction (5) were independent on the change of the C 2 F 4 pressure in the range of 1 to 13 mTorr, i.e., reaction (5) is first-order with the C 2 F 4 pressure. The average value of the rate constants in the range of 180῎310 K in Fig.…”
Section: Resultsmentioning
confidence: 73%
“…The formation of CF 3 ῌ as one of the major ions is a very important information in the plasma chemistry because this ion is known to act as a very e$cient etchant in the semiconductor fabrication. (5). That is, reactions (4) and (5) are highly exothermic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation